2012
DOI: 10.1037/a0025775
|View full text |Cite
|
Sign up to set email alerts
|

Generalizability of evidence-based assessment recommendations for pediatric bipolar disorder.

Abstract: Bipolar disorder is frequently clinically diagnosed in youths who do not actually satisfy DSM-IV criteria, yet cases that would satisfy full DSM-IV criteria are often undetected clinically. Evidence-based assessment methods that incorporate Bayesian reasoning have demonstrated improved diagnostic accuracy, and consistency; however, their clinical utility is largely unexplored. The present study examines the effectiveness of promising evidence-based decision-making compared to the clinical gold standard. Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 106 publications
0
21
0
Order By: Relevance
“…These findings underscore the importance of using semi-structured interviews, such as the K-SADS, with a collaborative consensus team approach (26, 27). The process of conducting a full diagnostic assessment ensures that the clinician goes through each Axis I module, and systematically considers the DSM-IV-TR criteria for each disorder.…”
Section: Discussionmentioning
confidence: 85%
“…These findings underscore the importance of using semi-structured interviews, such as the K-SADS, with a collaborative consensus team approach (26, 27). The process of conducting a full diagnostic assessment ensures that the clinician goes through each Axis I module, and systematically considers the DSM-IV-TR criteria for each disorder.…”
Section: Discussionmentioning
confidence: 85%
“…However, they can change the probability of a PBD diagnosis within an evidence-based medicine or Bayesian decision-making framework 111,112 and substantially improve the accuracy of clinical interpretation and agreement about next clinical action. 102,112 Some checklists have also shown sensitivity to treatment effects in masked randomized controlled trials (RCTs), with effect sizes equal to those based on direct interview of the youth and primary caregiver. 113,114 Checklists can improve diagnostic decision making in a range of clinical settings, as well as measuring treatment response.…”
Section: | Measurementmentioning
confidence: 99%
“…When clinicians do not know the base rate at their clinics, they can use a reported base rate at similar settings or start with a quantification of their clinical judgment. Using these methods produces large improvements in the accuracy and consistency of clinical interpretations (Jenkins et al, 2011), and increases agreement about the next clinical action that is indicated, even when the initial estimate is not accurate (Jenkins, Youngstrom, Youngstrom, Feeny, & Findling, 2012). …”
Section: Discussionmentioning
confidence: 99%